Research handbook on EU energy law and policy - Leal-Arcas, Rafael; Wouters, Jan, 1964-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
This authoritative Research Handbook presents, for the first time, a comprehensive overview of the most important research and latest trends in EU energy law and policy. It offers high-quality original contributions that provide state-of-the-art research in this rapidly evolving area, situated in the broader context of international economic law and governance. The Research Handbook covers the full breadth of topics and developments in the EU's law and policy regarding energy, fully acknowledging the multifaceted nature of this vast arena. It is divided into four broad thematic areas of EU energy law and policy: 1) institutional aspects; 2) external aspects; 3) economic, social and legal aspects; and 4) environmental and technological aspects. Expert contributors also present a future research agenda in these four areas and identify emerging themes with substantial potential for further research in years to come. Timely and engaging, the Research Handbook on EU Energy Law and Policy will be an indispensable reference point for academics, students, lawyers, economists, policymakers and think tanks in the field. It will also be of interest to those operating in other energy-related disciplines.
1. Introduction - Rafael Leal-Arcas and Jan Wouters -- Part I. Institutional aspects -- 2. Competences in EU energy policy / Kim Talus and Pami Aalto -- 3. External competences in energy and climate change / Ries Kamphof, Thijs Bonenkamp, Joren Selleslaghs and Madeleine O. Hosli -- 4. EU energy and competition / Leigh Hancher and Francesco Salerno -- 5. The European energy union / Thomas Pellerin-Carlin -- Part II. External aspects -- 6. The new global landscape and energy politics in the 21st century / Klaus Segbers -- 7. The role of the ECT in EU-Russia energy relations / Andrey Konoplyanik -- 8. Global energy security and EU energy policy / Severin Fischer -- 9. Rule-maker or rule-taker? The EU and the shifting global political economy of energy / Thijs Van de Graaf -- 10. The international energy charter: a new impetus for global energy governance? / Sijbren de Jong ---11. The EU energy security strategy in the Caspian Sea region: addressing the bear in the room / Stratos Pourzitakis -- 12. Russian energy projects and the global climate, geopolitics and development conundrum / Slawomir Raszewski -- Part III. Economic, social and legal aspects -- 13. The dark side of power: corruption and bribery within the energy industry / Costantino Grasso -- 14. Electricity and gas markets / Guy Block and Elvira Saitova -- 15. Energy justice / Jan Schmitz, Kai Menzel and Fabian Dittrich -- 16. Energy and law of the sea / Stephen Minas -- 17. Remediation of business-related human rights violations in the context of EU energy policy / Youseph Farah and Malakee -- 18. EU energy law in the maritime sector / Beatriz Huarte Melgar -- 19. A (legal) challenge to privacy: on the implementation of smart meters in the EU and the US / Max Baumgart -- 20. Paris agreement: the evolution of international law standards in the post-ontological framework / Antonio Morelli ---21. Social science as a starting point? / Michael Kattirtzi -- Part IV. Environmental and technological aspects -- 22. EU emissions trading scheme: preventing carbon leakage before and after the Paris Agreement / Kati Kulovesi -- 23. Energy and environment / Peter Vajda and József Feiler -- 24. Are smart grids the key to EU energy security? / Filippos Proedru -- 25. Renewable energy, waste management and the circular economy in the EU: solar PV and wind power / Feja Lesniewska -- 26. The role of renewable energy law and policy in meeting the EU's energy security challenges / Penelope Crossley -- 27. Energy futures: new approaches to energy choices / David Elliott -- 28. EU energy innovation policy: the curious case of energy efficiency / Jan Rosenow and Florian Kern -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: politiky Evropské unie; energetika; European policies; energy industries; země Evropské unie; European Union countries; e-knihy online; e-books online